circTAF8 Regulates Myoblast Development and Associated Carcass Traits in Chicken - Kan Li; Kan Li; Weichen Huang; Weichen Huang; Zhijun Wang; Zhijun Wang; Yangfeng Chen; Yangfeng Chen; Danfeng Cai; Danfeng Cai; Qinghua Nie; Qinghua Nie (Frontiers in Genetics, 2022)
Recent studies have shown that circular RNAs (circRNAs) play important roles in skeletal muscle development. CircRNA biogenesis is dependent on the genetic context. Single-nucleotide polymorphisms in the introns flanking circRNAs may be intermediate-inducible factors between circRNA expression and phenotypic traits. Our previous study showed that circTAF8 is an abundantly and differentially expressed circRNA in leg muscle during chicken embryonic development. Here, we aimed to investigate circTAF8 function in muscle development and the association of the SNPs in the circTAF8 flanking introns with carcass traits. In this study, we observed that overexpression of circTAF8 could promote the proliferation of chicken primary myoblasts and inhibit their differentiation. In addition, the SNPs in the introns flanking the circTAF8 locus and those associated with chicken carcass traits were analyzed in 335 partridge chickens. A total of eight SNPs were found associated with carcass traits such as leg muscle weight, live weight, and half and full-bore weight. The association analysis results of haplotype combinations were consistent with the association analysis of a single SNP. These results suggest that circTAF8 plays a regulatory role in muscle development. These identified SNPs were found correlated with traits to muscle development and carcass muscle weight in chickens.